Analysis of factors affecting the clinical management of infection in culture-negative patients following percutaneous endoscopic decompression: a retrospective study - Changpeng Qu; Haixin Wei; Hao Zhang; Zheng Lian; Hui Lu; Shuo Han (Frontiers in Cellular and Infection Microbiology)
BackgroundCulture-negative spinal infections after prophylactic antibiotic use in percutaneous endoscopic decompression are rare, and diagnostic difficulties and the risk of antibiotic-resistant infections complicate treatment. This study retrospectively analyzed the medical records of culture-negative patients following percutaneous endoscopic surgery to identify risk factors influencing antimicrobial therapy and provide insights for clinical management.MethodsData were retrospectively collected from patients who underwent lumbar percutaneous endoscopic decompression at the Affiliated Hospital of Qingdao University between January 2014 and June 2023. The patients’ medical records were reviewed. Patient demographics, hidden blood loss, daily blood glucose control, and maximum temperature during treatment were recorded as potential risk factors. C-reactive protein, procalcitonin, white blood cells, erythrocyte sedimentation rate, and the duration of antibiotic treatment were used as indicators of infection treatment. The impact of these risk factors on infection was then analyzed.ResultsThe results showed that blood glucose control was strongly correlated with the severity of infection (Beta = 0.60, P = 0.00), strongly correlated with short-term treatment effectiveness (Beta = 0.65, P = 0.00), and moderately correlated with the duration of antibiotic treatment (Beta = 0.41, P = 0.01). Hidden blood loss was moderately correlated with the severity of infection (Partial-R = 0.49, P = 0.00) and moderately correlated with the duration of antibiotic treatment (Partial-R = 0.48, P = 0.00). Hidden blood loss index was moderately correlated with the duration of antibiotic treatment (Partial-R = 0.50, P = 0.00). Female was a favorable factor to shorten the duration of antibiotic treatment (Beta = -0.25, P = 0.01), and higher maximum temperature during infection may indicate a longer duration of antibiotic treatment (Beta = 0.28, P = 0.02).ConclusionOur findings suggest that healthy blood glucose levels, a lower hidden blood loss and hidden blood loss index might help reduce the duration of antibiotic use after infection. Effective hemostasis during surgery to reduce hidden blood loss and good preoperative blood glucose control indicators are both beneficial measures for infection treatment.